2022
DOI: 10.1186/s12933-022-01457-0
|View full text |Cite
|
Sign up to set email alerts
|

Asprosin induces vascular endothelial-to-mesenchymal transition in diabetic lower extremity peripheral artery disease

Abstract: Background Altered adipokine secretion in dysfunctional adipose tissue facilitates the development of atherosclerotic diseases including lower extremity peripheral artery disease (PAD). Asprosin is a recently identified adipokine and displays potent regulatory role in metabolism, but the relationship between asprosin and lower extremity PAD remains uninvestigated. Methods 33 type 2 diabetes mellitus (T2DM) patients (DM), 51 T2DM patients with PAD (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…AR, aspect ratio; ASP, asprosin; BIN, binarization; Ctrl, control; FF, form factor; PA, palmitic acid; RTAEC, rat thoracic aortic endothelial cell. ***p < 0.001 vs. Ctrl group; ### p < 0.001 vs. PA group; $$ p < 0.01, $$$ p < 0.001 vs. ASP group [Color figure can be viewed at wileyonlinelibrary.com] participated in the vascular dysfunction of lower-extremity PAD [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AR, aspect ratio; ASP, asprosin; BIN, binarization; Ctrl, control; FF, form factor; PA, palmitic acid; RTAEC, rat thoracic aortic endothelial cell. ***p < 0.001 vs. Ctrl group; ### p < 0.001 vs. PA group; $$ p < 0.01, $$$ p < 0.001 vs. ASP group [Color figure can be viewed at wileyonlinelibrary.com] participated in the vascular dysfunction of lower-extremity PAD [15].…”
Section: Discussionmentioning
confidence: 99%
“…The injury and dysfunction of vascular endothelial cells (ECs) induced by hyperglycemia and/or hypertriglyceridemia are the first triggers for blood vessel dysfunction in obesity [12]. Coincidentally, recent studies have shown that ASP is involved in cardiovascular diseases (CVD) [13,14] and that pathologically elevated ASP levels may be an independent risk factor for lower-extremity peripheral arterial disease (PAD) [15]. Mitochondria are the main organelles in charge of cell energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a significant asprosin levels were detected in T2DM patients with carotid plaque compared to non-carotid plaque T2DM group ( 74 ). Furthermore, elevated plasma asprosin levels was reported in T2DM patients suffering from diabetic lower extremity peripheral artery disease (PAD) ( 73 ). Asprosin induced TGF-β signaling pathway activation that directly affects endothelial-to-mesenchymal transition (EndMT) ( 73 ).…”
Section: Asprosin In Diabetic Complicationsmentioning
confidence: 99%
“…Furthermore, elevated plasma asprosin levels was reported in T2DM patients suffering from diabetic lower extremity peripheral artery disease (PAD) ( 73 ). Asprosin induced TGF-β signaling pathway activation that directly affects endothelial-to-mesenchymal transition (EndMT) ( 73 ).…”
Section: Asprosin In Diabetic Complicationsmentioning
confidence: 99%
“…Asprosin is a novel hormone discovered in 2016 is secreted by the white adipose tissue of the body (8). Asprosin, is expressed by the gene Fibrillin1, present in most cells of the body including human cutaneous fibroblasts, pancreatic B cells, peripheral tissues and organs (8,9,10). Asprosin, has been shown to be associate in metabolic disorders such as cardiovascular disease, diabetes, polycystic ovarian syndrome, obesity and implicated as a diagnostic biomarker in these disorders (11).…”
Section: Introductionmentioning
confidence: 99%